Evaluación del tratado de libre comercio entre Colombia y Chile durante el periodo 2009-2016 (2019)
The Free Trade Agreements have been the center of discussion when evaluating the behavior of the Colombian economy, the effects derived from them help us to estimate if it is a true growth in the different sectors of the economy, in view of the importance that the commercial relationship that the country has had with Chile and based on the statements made in the account at the time of signing the treaty and the results of the entry into force of the treaty. The results of the free trade agreement between Colombia and Chile, in order to provide a study reference for free trade states.